Qaraqorum’s Afterlife: Centres and Peripheries in the late Yuan and early Ming Periods - Fiaschetti, Francesca (Acta Mongolica, 2022)
The capital of the Mongol Empire, due to its favourable location, was not only the symbolic centre of power for the medieval Mongols, but also performed several key functions in the political, economic, and military administration of the empire. Throughout the thirteenth century, and even after the city’s decline in the fourteenth century, its strategic and ideological value remained undisputed. Control of the region around Qaraqorum, therefore, became a prerogative for all those who wanted to dominate the Yuan territories and claim the legacy of the Mongol empire. By examining some Chinese sources of the period, the article shows how shaping a linkage with Mongolia, in terms of symbolic geography as well as words of power, remained a fundamental priority of the emperors ruling over East Asia well beyond the mid-fourteenth century and the end of the Yuan dynasty.